Suppression of proinvasive RGS4 by mTOR inhibition optimizes glioma treatment - Weiler, Markus; Pfenning, Philipp-Niclas; Blaes, Jonas; Jestaedt, Leonie; Berger, Benjamin; Combs, Stephanie; Deimling, Andreas von; Bendszus, Martin; Platten, Michael; Wick, Wolfgang (Oncogene, 2013)
An essential mode of acquired resistance to radiotherapy (RT) appears to be promotion of tumor cell motility and invasiveness in various cancer types, including glioblastoma, a process resembling ‘evasive resistance’. Hence, a logical advancement of RT would be to identify suitable complementary treatment strategies, ideally targeting cell motility. Here we report that the combination of focal RT and mammalian target of rapamycin (mTOR) inhibition using clinically relevant concentrations of temsirolimus (CCI-779) prolongs survival in a syngeneic mouse glioma model through additive cytostatic effects. In vitro, the mTOR inhibitor CCI-779 exerted marked anti-invasive effects, irrespective of the phosphatase and tensin homolog deleted on chromosome 10 status and counteracted the proinvasive effect of sublethal irradiation. Mechanistically, we identified regulator of G-protein signaling 4 (RGS4) as a novel target of mTOR inhibition and a key driver of glioblastoma invasiveness, sensitive to the anti-invasive properties of CCI-779. Notably, suppression of RGS4-dependent glioma cell invasion was signaled through both mTOR complexes, mTORC1 and mTORC2, in a concentration-dependent manner, indicating that high doses of CCI-779 may overcome tumor-cell resistance associated with the sole inhibition of mTORC1. We conclude that combined RT and mTOR inhibition is a promising therapeutic option that warrants further clinical investigation in upfront glioblastoma therapy.
Published online 7 May 2012
Gesehen am 06.05.2019